VISUAL EXPLORATION OF SUNFLOWERS AS THE IDEA OF CREATING PAINTINGS - Hanifa Sa'diyah (CILPA, 2020)
The aim of this senior commitment is to get to know more about sunflowers such as sunflowers from Indonesia but can flourish in Indonesia, known by different names in Indonesia according to the region, how to live sunflowers, how long it takes , its flower characteristics, and its uniqueness that follows the direction of the sun, and then many lessons can be taken from sunflowers. This makes the author interested in better understanding Sunflowers and Making Sunflowers as the basic idea for making artworks with the theme "Eksplorasi Visual Bunga Matahari Sebagai Ide Penciptaan Karya Seni Lukis". The author wants to visualize sunflowers not as suggested, which is poured in a more imaginative and creative work without removing the characteristic or still being able to discuss it as sunflowers and linking its meaning to human beings.           The methods used by the author are: 1). Exploration exploration or searching for new things on a new visit. By exploring ideas, concepts, visual forms, media, techniques, and aesthetics. 2). The design is making sketches with pencils on HVS paper media. 3). Design sketches, works used in visual works of inventions, methods for finding ideas in collections of objects.           The work created by the writer in this final project consists of 7 works with canvas media. The concept in the author's painting is to produce the embodiment of sunflowers in different forms by placing them between objects or being used rather than in reality. The outputs are, among others, "Jangan Menilai Dari Yang Terlihat (110 x 100 cm), Kesabaran Kaktus (100 x 80 cm), Senja Datang Waktunya Pulang(130 x 90 cm), Keluar Dari Zona Nyaman (110 x 90 cm), Berlalu Tanpa Berulang (110 x 100 cm), Broken Is'nt Bad (100 x 70 cm), Dream Catcher (100 x 80 cm) ".